Synthesis of new low-viscous sulfonic acid-functionalized ionic liquid and its application as a Brönsted liquid acid catalyst for the one-pot mechanosynthesis of 4H-pyrans through the ball milling process - Khaligh, Nader Ghaffari; Mihankhah, Taraneh; Johan, Mohd Rafie (Elsevier, 2019)
In the present study, a new low-viscous sulfonic acid-functionalized ionic liquid (SAIL) viz. 4,4′-trimethylene-N,N′-sulfonic acid-dipiperidinium chloride was synthesized and characterized by FTIR, 1D and 2D NMR, and Mass spectra. Then, some properties of new SAIL were determined including pH, viscosity, density, and solubility in some common solvents. The catalytic activity of new SAIL was demonstrated for the one-pot mechanosynthesis of pyrano[4,3-b]pyrans, dihydropyrano[3,2-c]chromene and tetrahydrobenzo[b]pyrans using planetary ball mill under solvent-free conditions. This current mechanosynthesis methodology for the synthesis of 4H-pyran-annulated heterocyclic scaffolds displays a combination of the synthetic virtues of conventional multi-component reaction with ecological benefits and convenience of a simple mechanocatalytic procedure. New SAIL was easily recycled and reused several times with no significant loss of activity.